Do borrower rights improve borrower outcomes? Evidence from the foreclosure process - Kristopher Gerardi; Lauren Lambie-Hanson; Paul S. Willen (Federal Reserve Bank of Boston, 2011)
The authors evaluate laws designed to protect borrowers from foreclosure. They find that these laws delay but do not prevent foreclosures. They first compare states that require lenders to seek judicial permission to foreclose with states that do not. Borrowers in judicial states are no more likely to cure and no more likely to renegotiate their loans, but the delays lead to a buildup in these states of persistently delinquent borrowers, the vast majority of whom eventually lose their homes. They next analyze a right-to-cure law instituted in Massachusetts on May 1, 2008. Using a difference-in-differences approach to evaluate the effect of the policy, they compare Massachusetts with neighboring states that did not adopt similar laws. They find that the right-to-cure law lengthens the foreclosure timeline but does not lead to better outcomes for borrowers.
Keywords: G21; K11; R31; 330; foreclosure; mortgage; judicial; power of sale; right to cure